Descartes and the puzzle of sensory representation - De Rosa, Raffaele (Oxford : Oxford University Press, 2010)
Offering a novel account of the representationality of Cartesian sensations, this text places Descartes' theory of sensation in the central position it deserves among the philosophical and scientific investigations of the workings of the human mind.
Description based on print version record.
Includes bibliographical references.
Keywords: d; Perception; Senses and sensation -- Philosophy